Le graphe et la graphie de la Terre. Un exercice formel pour commémorer le bicentenaire du Voyage aux Amériques équinoxales - Hervé Gazel (Unité Mixte de Recherche 8504 Géographie-cités, 1999)
This paper examines the migration of geographical knowledges from paper to computer. It is possible to conceive this migration as an hypertextualization. The explanation of the links between graph and geographical writing is necessary. The example of the classification of the climate which sends back to the Humboldt work’s could be used to show how the mutation of geographical knowledges is linked to the analysis of the relation between graph and graphie de la terre.